A Mixed-apprOach program To help women wIth breast cancer stay actiVE (MOTIVE program): A pilot-controlled study. Issue 11 (November 2021) - Natalucci, Valentina; Lucertini, Francesco; Vallorani, Luciana; Brandi, Giorgio; Marchegiani, Manuela; Pistelli, Mirco; Berardi, Rossana; Ceravolo, Maria Gabriella; Barbieri, Elena; Capecci, Marianna
Abstract: Given the benefits of physical activity for breast cancer survivals, this pilot study aims to assess the feasibility of the MOTIVE program at achieving and maintaining the recommended physical activity level in women diagnosed and treated breast cancer, over 16 weeks. We conduct a pilot-controlled study of 20 women diagnosed with breast cancer stage I, II or IIIa. In this study, women of Intervention Arm (n = 10) received the MOTIVE program. This group was compared to women of Control Arm (n = 10) who received only counselling. Health-related fitness measures, and quality of life were assessed at baseline (t0) and after 4 (t1), 8 (t2) and 16 (t3) weeks. Intervention Arm women reached the recommended physical activity guidelines at t1 and t2 (eff.size = 1.9 [1.0–3.1]), and 90% continued to be active, autonomously, at t3 (eff.size = 1.12 [0.21–2.12]). Intervention Arm participants' arm strength, fitness levels and quality of life also improved over time. No significant improvements in outcome measures were observed in Control Arm participants. These results are encouraging and suggest that the MOTIVE program may be a viable, well tolerated and effective option to help breast cancer women reaching a stable physical activity level over time, which meets prevention-related goals. Abstract : Physical activity; Adherence; Breast cancer; Aerobic exercise; Strength training; Secondary/tertiary prevention; Lifestyle; Public health.